Perancangan Sistem E-Commerce pada UMKM Penjualan pakaian wanita Menggunakan Opencart di Kec. Padang Gelugur - Nuraisyah, Nuraisyah; Annas, Firdaus; Sipayung, Nurul Hidaya (JOVISHE : Journal of Visionary Sharia Economy, 2023)
This article aims to design and develop a practical and efficient e-commerce system to support clothing sales activities at Micro, Small and Medium Enterprises (MSMEs) in Pasaman Regency. By utilizing the opencart application platform. The system is expected to facilitate the transaction process, expand market reach, and increase the competitiveness of MSMEs in the digital era. The sale of clothes used in MSMEs selling clothes is still traditional and the online media used also does not exist such as promotion on social media, even though current technological advances are very rapid which can encourage the use of technology to create sales media and promote products globally.  This research adopts the Research End Development (R&D) approach by referring to the 4D development model. This model consists of 4 main stages, namely defining, designing, developing, and disseminating. Each of these stages is passed systematically to ensure the final product, namely the e-commers system, which can meet the needs of MSMEs and provide optimal benefits. The results of this study are in the form of a web-based e-commers media using opencart applications that are valid, practical and effective. The findings in this study found that opencart can be used as a platform for selling clothes as a medium in increasing the results in MSMEs selling clothes in the padang gelugur sub-district.